Muscle stiffness and injury effects of whole body vibration - Cronin, John B.; Oliver, Melody; McNair, Peter J. (Physical therapy in sport, 2004)
Objective. The interest in vibration as a method of enhancing muscular performance is receiving considerable attention from sport scientists, physiotherapists, coaches and athletes. Increases in strength, power and jump height have been reported after a single session of whole body vibration. In some cases, this immediate change has been attributed to changes in the stiffness of the musculotendinous complex without directly measuring the stiffness properties of muscle. The aim of this study was to determine whether whole body vibration had an effect on the stiffness of the triceps surae muscle group. Design. The stiffness of the right and left leg of 11 relatively untrained subjects was measured prior to a warm-up, post-warm-up and post-vibration using a damped oscillation technique. After warm-up, one leg was vibrated (frequency 26 Hz, amplitude 6 mm) whilst the other leg acted as a control. The subjects were exposed to the vibration five times for a duration of 60 s with a 60 s rest between each repetition. Results. No significant differences ( P>0.05) in stiffness were found between the baseline measures and the post-warm-up and post-vibration measures of stiffness. Following vibration a number of subjects experienced pain to the lower leg muscles and a loss of function. In some subjects, the pain was experienced at the jaw and the neck. These symptoms required treatment in six subjects but the pain had resolved within 7–10 days in all subjects. Conclusions. It appears that vibratory stimulation loading parameters used to enhance performance do not significantly alter muscle stiffness in untrained individuals. Considering the injury potential associated with whole body vibration further research into safe dose-response relationships is recommended.